Customs unions and national budgets - Pertti Haaparanta (Bank of Finland, 1988)
It is shown that the Dixit-Norman argument for the creation of an optimal customs union without lump sum transfers presupposes either that there exists a joint fiscal authority in the union or that lump sum transfers between national governments are possible. A necessary and sufficient condition for the decentralized implementation of the optimal union is derived. This condition is related to the old discussion of trade creation vs. trade diversion. The other contribution of the paper is to extend the Dixit-Norman argument to customs unions with factor mobility i.e. to common markets.
URN:NBN:fi:bof-201908051328
Keywords: 330